ANALYSIS OF STUDENTS' MISCONCEPTIONS IN CLASS XI MIPA 4 OF HIGH SCHOOL 6 MAKASSAR ON BUFFER SOLUTION USING THE THREE-TIER DIAGNOSTIC TEST INSTRUMENT - Majid, Ahmad Fudhail; Jusniar, Jusniar; Nursyamsi, Nursyamsi (Universitas Negeri Surabaya, 2023)
This study aims to describe students’ misconceptions and the causes of class XI MIPA 4 SMA Negeri 6 Makassar in the buffer solution material. The subjects in this study were students of class XI MIPA 4 SMA Negeri 6 Makassar in 2021/2022 academic year which consisted of 27 students and had studied the buffer solution material. The research instrument used in this study is a diagnostic test, namely Three Tier Multiple Choice which is supported by interview data. The results showed that percentage of students' misconceptions in the buffer solution material occurred in: 1) concept’s understanding 71.6%; 2) The properties 70.4%; 3) The components 72.2%; 4) The pH Calculating 49.1%; 5) the work principle 50.0%; and 6) the function of our life of 50.6%. Factors that cause misconceptions in students are those that come from the students themselves.